Inheritance of RAPD and ISSR marker in inter-specific coffee hybrids (Coffea congensis Froehner x Coffea canephora Pierre) and their derivatives: Implications for genetic improvement - Kumar, Deepanshu; Nandhini, Bharatha; Rao, Surya Prakash; Sivamani, Karthiga; Sethuraman, Thilaga; Doss, Ganesh (Journal of Plantation Crops, 2025)
The C x R coffee hybrid (a cross between Coffea congensis and Coffea canephora) represents a significant development in coffee cultivation in India, addressing challenges like plant size optimization for high-density planting and enhancement of beverage quality. However, maintaining genetic purity in this hybrid is challenging due to genetic segregation caused by cross-pollination with other diploid species or within the hybrid itself. This highlights the need for effective tools like DNA marker-assisted selection (MAS) to improve the genetic stability and performance of this hybrid. In this study, two dominant DNA markers (RAPD and ISSR) were analyzed for their utility in coffee genetic improvement. Out of 24 RAPD primers and 15 ISSR primers tested, only 3 RAPD and 5 ISSR primers were effective in discriminating the parental species.These selective RAPD and ISSR primers produced nine and twenty threepolymorphic bands with size range of 400 bp – 1200 bp for RAPD and 100 bp – 2000 bp for ISSR, respectively. Species specific RAPD and ISSR markers were found in female (Coffeacongensis) and male (Coffeacanephora) parent of the hybrid. Some of these markers were successfully inherited by F1 hybrids and backcross progenies.The suitability of the primers for MASwas evaluated based on the parameters such as Polymorphic information content (PIC), effective multiplex ratio (EMR), marker index (MI) and resolving power (RP). The selected RAPD and ISSR markers enable effective discrimination between the parental species and their hybrids. This is crucial for ensuring the genetic purity of seeds and plants.The ability to use MAS for maintaining seed purity and selecting superior hybrids can significantly enhance the productivity and quality of C x R coffee hybrids, benefiting the coffee industry.The importance of these markers in genetic improvement of this hybrid is discussed.